2008
DOI: 10.1063/1.3048544
|View full text |Cite
|
Sign up to set email alerts
|

A short working distance multiple crystal x-ray spectrometer

Abstract: For x-ray spot sizes of a few tens of microns or smaller, a millimeter-sized flat analyzer crystal placed approximately 1 cm from the sample will exhibit high energy resolution while subtending a collection solid angle comparable to that of a typical spherically bent crystal analyzer (SBCA) at much larger working distances. Based on this observation and a nonfocusing geometry for the analyzer optic, we have constructed and tested a short working distance (SWD) multicrystal x-ray spectrometer. This prototype in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…The curvature itself does not significantly affect instrumental resolution since the curved focal line can be taken into account to produce a spectrum, as is commonly done in synchrotron implementations. 40,54,56 In the present spectrometer in the laboratory setting, however, the curvature of the signal convolved with the large spot illumination results in irreversible blurring of the ideal point-source response function for regions of the sensor far out of the Rowland plane. In order to maintain high resolution for lab-based measurements, this requires that the signal on the detector be cropped around the region centered on the Rowland plane to exclude these blurred regions.…”
Section: Experimental a Laboratory Environmentmentioning
confidence: 99%
“…The curvature itself does not significantly affect instrumental resolution since the curved focal line can be taken into account to produce a spectrum, as is commonly done in synchrotron implementations. 40,54,56 In the present spectrometer in the laboratory setting, however, the curvature of the signal convolved with the large spot illumination results in irreversible blurring of the ideal point-source response function for regions of the sensor far out of the Rowland plane. In order to maintain high resolution for lab-based measurements, this requires that the signal on the detector be cropped around the region centered on the Rowland plane to exclude these blurred regions.…”
Section: Experimental a Laboratory Environmentmentioning
confidence: 99%
“…It was demonstrated that based on a multiple-crystal array affixed on a spherical substrate, a good energy resolution and a large solid collection angle can be achieved. [37][38][39] The use of diced or segmented-type optics leads to a simple spectrometer that is easy to implement for any scattering geometry.…”
Section: Introductionmentioning
confidence: 99%
“…The XANES technique provides a methodology by which Ce 3+ /Ce 4+ in Ti-rich materials can be determined. The recently developed Minixs high-energy resolution X-ray fluorescence analyzer, which uses flat crystals in a quasi-Johann or von Hamos arrangement in conjunction with a two-dimensional position-sensitive detector to measure a range of emission energies for a given incident energy, will greatly facilitate this kind of analysis in the future (Dickinson et al 2008;Mattern et al 2012).…”
Section: Recommendations For Future Workmentioning
confidence: 99%